1980
DOI: 10.1111/j.1471-4159.1980.tb12497.x
|View full text |Cite
|
Sign up to set email alerts
|

The γ‐Aminobutyrate Content of Nerve Endings (Synaptosomes) in Mice After the Intramuscular Injection of γ‐Aminobutyrate‐Elevating Agents: A Possible Role in Anticonvulsant Activity

Abstract: The intramuscular administration of L-cycloserine, gabaculine, and aminooxyacetic acid caused significant, time-dependent increases in the gamma-aminobutyric acid (GABA) content of both whole brain and synaptosomal-enriched preparations obtained from the tissue, a linear relationship being observed between the two parameters. In contrast, the administration of hydrazine resulted in a large increase in whole brain GABA level, with little change in the synaptosomal GABA content. The key factor in these different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
15
0

Year Published

1981
1981
1989
1989

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(18 citation statements)
references
References 16 publications
3
15
0
Order By: Relevance
“…Thus the degree of elevation and values for the synthesis rate of GABA in different brain regions were similar to those obtained by Collins (1972), Pericic et al (1977), Wood et al (1980), Carmona et al (1980 and Bernasconi et 5.14 ± 0.67 (6) 5.20 ± 0.72 (6) 6.43 ± 0.67 (5) 6.60 ± 0.25 (5) 7.50 ± 0.67 (6) 8.50 ± 0.73 (6) 13.18 ± 0.96 (6) 11.60±0.68 (6) 18.40 ± 0.24 (5) 18.18 ± 0.45 (5) 24.80 ± 0.45 (6) al. (1982).…”
Section: Discussionsupporting
confidence: 86%
“…Thus the degree of elevation and values for the synthesis rate of GABA in different brain regions were similar to those obtained by Collins (1972), Pericic et al (1977), Wood et al (1980), Carmona et al (1980 and Bernasconi et 5.14 ± 0.67 (6) 5.20 ± 0.72 (6) 6.43 ± 0.67 (5) 6.60 ± 0.25 (5) 7.50 ± 0.67 (6) 8.50 ± 0.73 (6) 13.18 ± 0.96 (6) 11.60±0.68 (6) 18.40 ± 0.24 (5) 18.18 ± 0.45 (5) 24.80 ± 0.45 (6) al. (1982).…”
Section: Discussionsupporting
confidence: 86%
“…Although there is convincing evidence in support of a relationship between the excitable state of the brain and the GABA content of nerve ending (Sarhan & Seiler, 1979;Wood et al, 1980;Wood, 1981), and the theory that the onset of seizures induced by various convulsants is associated with a decrease in the content of GABA or an increase in the content of glutamate (Geddes & Wood, 1984), such findings don't stand for hypoglycemic convulsion since both glutamate and GABA were decreased during preconvulsive, convulsive and postconvulsive stages.…”
Section: Discussionmentioning
confidence: 99%
“…The L-isomer of 4-amino-3-isoxazolidinone (L-cycloserine) is a potent inhibitor of transaminases, especially y-aminobutyrate-transaminase (GABA-T; EC 2.6.1.19) (Severin et al, 1968;Wood et al, 1980), alanine transaminase (EC 2.6.1.2) (Profirieva and Kivman, 1967;Wong et al, 1972;Wood et al, 1978), and aspartate transaminase (EC 2.6.1.1) (Karpeisky and Breusov, 1965), and has widely been used to study the mechanisms of transamination (Karpeisky and Breusov, 1965;Churchich, 1967). Karpeisky and Breusov (1965) proposed inhibitory mechanisms of this compound on aspartate transaminase.…”
mentioning
confidence: 99%
“…The drug is therefore expected to be effective in elevating the brain GABA level and, at the same time, in lowering the concentrations of glutamate and aspartate, two putative excitatory neurotransmitters. Earlier studies have shown that intraperitoneal injection of this substance in rats delays the onset of seizures induced by strychnine, metrazol, and isonicotinic acid hydrazide (Monaco, 1958;Scotto et al, 1963;Wood et al, 1980). Correlated with this diminished susceptibility to seizures are a pronounced inhibition of GABA-T activity (Wood et al, 1978) and an increase in the GABA content of both whole brain and the synaptosomal fraction (Wood et al, 1980).…”
mentioning
confidence: 99%
See 1 more Smart Citation